Synthesis, Characterization and Biosensing Application of Photon Upconverting Nanoparticles - Kumar, Manoj (2009)
Phosphor/fluorescent molecules/particles have been widely used in various applications for quite some time. Typically, light with longer wavelength(s) is emitted when excited by shorter wavelength light. The opposite effect also exists, where a phosphor particle is excited with an infrared or red light and emits color(s) of shorter wavelengths, a process called up-conversion. Materials with upconverting properties have narrower absorption and line emission spectra than their down-converting counterparts. Because most non-target materials in a complex mixture do not possess such photon up-conversion properties, a dramatically improved S/N ratio is expected in sensing and luminescence reporting applications. This makes photon upconverting materials ideal for identification of trace amounts of target molecules. Here we report the synthesis, characterization and DNA detection application based on NaYF(4):Yb(3+), Er(3+) photon upconverting nanoparticles. The design of a nucleotide sensor for the detection of point mutation associated with sickle cell disease is described. The underlying principle for the detection is luminescence resonance energy transfer (LRET), with the photon upconverting nanoparticle as the donor and a dye, N,N,N′,N′-tetramethyl-6-carboxyrhodamine (TAMRA), as the acceptor. The detection scheme is based on a sandwich-type hybridization format. The presence of the target DNA is indicated by the increase of the normalized acceptor’s emission. Based on photon upconverting nanoparticles, which display high S/N ratio and no photobleaching, the DNA sensor demonstrates high sensitivity and specificity. The results demonstrate great potential of such nanomaterials as oligonucleotide sensors.